Three Libyan poets of the 20th century a study of their political poetry - Abu Dib, Sed M. (Durham University, 1980)
The present study consists of three parts, together with\anthology of Libyan political poetry Its aim is to deal with the surviving political works of three well-known modern poets, Ahmad al-Sharif, Ahmad Rafiq and Ahmad Qanabah To be precise, it deals only with their political works which were composed during the Italian and British occupations from 1911 to 1951The first part provides biographical sketches of the above- mentioned poets, their career and circumstances Chapter I deals with Ahmad al-Sharif's life, the second with Ahmad Rafiq's and the third with Ahmad Qanabah's Because their lives spanned the second half of the nineteenth and the first half of the twentieth centuries, the second part gives a comprehensive picture of the environment in which the poets lived. Chapter I describes Libya under the second Ottoman period from 1835 to 1911, paying particular attention to certain historical events which helped in developing political life in Libya at the time Chapter II and III deal with the Italian and British occupations from 1911 to 1951, laying great emphasis on the socio-economic, educational and political conditions as the main factors which formed their outlook and personality and affected their poetry In the light of these two parts, the third part studies the political trends in their poetry, Ottomanism and Islam, patriotism and Arabism successively In Chapter I a general survey is made on the development of modern Libyan poetry Chapter II examines the Ottoman and Islamic trend in their works Chapter III deals with the patriotic trend Chapter IV studies the trend of Arabisn Finally, Chapter V assesses the aesthetic value of their political poetry and Its style
Keywords: Littérature – Libye